2022
DOI: 10.1002/pro.4390
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the pH dependence of the SARS‐CoV‐2 complete fusion domain and the role of its unique structural features

Abstract: SARS-CoV-2 may enter target cells through the process of membrane fusion at either the plasma ($pH 7.4-7.0) or endosomal ($pH 6.5-5.0) membrane in order to deliver its genetic information. The fusion domain (FD) of the spike glycoprotein is responsible for initiating fusion and is thus integral to the viral life cycle. The FD of SARS-CoV-2 is unique in that it consists of two structurally distinctive regions referred to as the fusion peptide (FP) and the fusion loop (FL); yet the molecular mechanisms behind ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…The exact location of the FP is a matter of debate, but there is a wide consensus that the putative fusion peptide region resides near the cleavage site S2' of SARS-CoV-2: FP1 (816-837), FP2 (835-856, also known as the fusion loop (FL) or fusion peptide proximal region (FPPR)), FP3 (854-874), and FP4 (885-909). [14,15] Recently Santamaria et al measured the membrane binding of all the fusion regions and found that FPPR (or FP2) and FP3 weakly interacted with the membrane, whereas FP1 and FP4 bind to the membrane strongly. [14] A shorter 18-residue analog of FP1 (816-833, now onwards termed as FP) was earlier identified as the fusion peptide.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The exact location of the FP is a matter of debate, but there is a wide consensus that the putative fusion peptide region resides near the cleavage site S2' of SARS-CoV-2: FP1 (816-837), FP2 (835-856, also known as the fusion loop (FL) or fusion peptide proximal region (FPPR)), FP3 (854-874), and FP4 (885-909). [14,15] Recently Santamaria et al measured the membrane binding of all the fusion regions and found that FPPR (or FP2) and FP3 weakly interacted with the membrane, whereas FP1 and FP4 bind to the membrane strongly. [14] A shorter 18-residue analog of FP1 (816-833, now onwards termed as FP) was earlier identified as the fusion peptide.…”
Section: Introductionmentioning
confidence: 99%
“…The NMR structure of FP-FPPR regions are solved in bicelles, which reports that FPPR or FP2) mostly resides at the lipid-water interface and does not embed into the membrane. [15,22,23] As a class-I fusion protein, after the cleavage at the S2' site by TMPRSS2, the FP region will be exposed to the membrane for interaction and perturbation. These observations led us to investigate the efficiency of membrane fusion by the FP.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations